Sevelamer inhibits the formation of cholesterol gallstones by modulating bile acid metabolism - Shen, Shuang; Ning, Min; Li, Muhan; Qian, Shengnan; Ye, Xin; Zhuang, Qian; Wu, Shan; Wan, Xinjian; Dong, Zhixia (Frontiers in Pharmacology, 2026)
BackgroundThe purpose of this study was to investigate the effect and mechanism of Sevelamer hydrochloride (Sev) on cholesterol gallstone formation via the intestinal Fxr-Fgf15 signaling pathway in a mouse model.MethodsA cholesterol gallstone mouse model was established. Mice were divided into groups treated with Sev, Fxr agonist, or controls. The incidence and severity of gallstones, along with liver/body weight ratio, were recorded. Total cholesterol (TC) and total bile acid (TBA) levels were measured. Biliary cholesterol supersaturation index (CSI) was calculated. Serum ALT and AST levels were quantified by ELISA. The expression of Fxr-Fgf15 pathway-related molecules and bile acid transporters were detected by RT-PCR and Western blot. Targeted bile acid metabolomics characterized ileal bile acid profiles, while metagenomics assessed gut microbiota alteration.ResultsSev treatment reduced hepatic lipid deposition, lowered biliary CSI, attenuated gallbladder wall thickening, improved liver function, and decreased TC levels. Mechanistically, Sev inhibited the intestinal Fxr-Fgf15 pathway, promoting hepatic bile acid synthesis and altering ileal bile acid composition. Fxr agonist reversed these effects, increasing Fgf15/Shp expression, suppressing bile acid synthesis, elevating CSI, and partially restoring gallstone susceptibility. Sev reshaped gut microbiota diversity, reducing Blautia and enriching Bacteroidales and Roseburia at genus level. Concurrently, Sev modulated the ileal bile acid pool, decreasing Fxr-activating bile acids and increasing Fxr-antagonizing bile acids. Microbiota-bile acid correlation analysis highlighted significant associations between specific taxa and bile acid profiles.ConclusionSev might prevent cholesterol gallstone formation by inhibiting the intestinal Fxr-Fgf15 pathway, promoting hepatic bile acid synthesis, reducing biliary cholesterol supersaturation, and restoring gut microbiota balance.